2013
DOI: 10.1007/s10843-013-0105-1
|View full text |Cite
|
Sign up to set email alerts
|

The internationalization of small firms: The relationship between the global mindset and firms’ internationalization behavior

Abstract: Some firms in internationally oriented industries are internationalized while other comparable firms in the same sector or industry do not. Observing this difference in strategic behavior among small firms led us to consider how differences in CEOs' attitudes, international orientation, and mindset might explain it. Therefore, this study adopts a cognitive perspective on management to explore the formation of the global mindset and the relationship between the global mindset of small-firm decision makers and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 83 publications
7
74
0
4
Order By: Relevance
“…For example, a considerable number of studies have been published on the relationship between entrepreneurial orientation (EO), namely the combination of key behaviors (innovativeness, proactiveness, and risk-taking) that drive entrepreneurial activity, and IE indicating that high levels of EO lead to international activity (Jantunen et al 2005;Joardar and Wu 2011;Ripollés-Meliá et al 2007). Additionally, in recent years, several authors have focused on the concept of a global mindset (GM), seen as a cognitive capability represented by the curiosity for and understanding of actions that support the identification entrepreneurial opportunities in a global setting, to explain international entrepreneurial behavior Kyvik et al 2013). This paper investigates the combination of these two concepts as an indicator for EIT in different contexts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a considerable number of studies have been published on the relationship between entrepreneurial orientation (EO), namely the combination of key behaviors (innovativeness, proactiveness, and risk-taking) that drive entrepreneurial activity, and IE indicating that high levels of EO lead to international activity (Jantunen et al 2005;Joardar and Wu 2011;Ripollés-Meliá et al 2007). Additionally, in recent years, several authors have focused on the concept of a global mindset (GM), seen as a cognitive capability represented by the curiosity for and understanding of actions that support the identification entrepreneurial opportunities in a global setting, to explain international entrepreneurial behavior Kyvik et al 2013). This paper investigates the combination of these two concepts as an indicator for EIT in different contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Gupta and Govindarajan (2002) or Levy et al (2007) focused on concepts like cosmopolitanism and cognitive complexity in the international business context. However, studies explicitly linking managerial mindsets and characteristics to MNE performance are even less frequent (e.g., Felício et al, 2012;Kyvik, Saris, Bonet, & Felício, 2013;Nummela et al, 2004).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…For instance, Rialp et al (2005) argue that the small firm's founder(s) and the founding team's characteristics, international vision, prior international experience, managerial commitment and networking capability are important factors, which enable an instant type of internationalization. Kyvik et al (2013) find that the global mindset, cognitive flexibility and networking capability of the CEO and key decision-makers in the small business determine the level of instant internationalization of their small firms compared with other small firms from the same industry. Note that the entrepreneur and TMT are both important participants and technology (means) in the firms (see Figure 2.1) to carry out important tasks during internationalization.…”
Section: Inputs and Influence From The Individual Levelmentioning
confidence: 95%
“…The individual level inputs are put as the primary layer of the means pool (see the inner layer of Figure 2.2) in the analysis framework. International vision and attitude (Kyvik et al, 2013; 48 2. THEORETICAL FRAME Ruzzier et al, 2006), human capital with international knowledge and skills (Felício et al, 2012;Evers and O'Gorman, 2011), and TMT's social capital (Zhou et al, 2007;Ellis, 2011), are the three important elements identified in earlier literature at this level.…”
Section: Inputs and Influence From The Individual Levelmentioning
confidence: 99%